Allergy and COVID-19 - De Filippo, Maria; Votto, Martina; Brambilla, Ilaria; Castagnoli, Riccardo; Montagna, Lorenza; Caffarelli, Carlo; Cardinale, Fabio; Miraglia Del Giudice, Michele; Tosca, Mariangela; Caimmi, Silvia; Licari, Amelia; Marseglia, Gian Luigi (Acta Biomedica Atenei Parmensis, 2021)
The first cases of as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection have been reported in Wuhan, China in December 2019. The World Health Organization declared the global pandemic in March 2020. Coronavirus disease 2019 (COVID-19) showed high rates of mortality in the adult population, whereas a mild course was observed in childhood. Allergic diseases, characterized by a type-2 polarization of the immune system, were considered one of the major risk factor of severe COVID-19. Large amounts of clinical data and expert opinions have been collected since the pandemic outbreak. This review summarizes the latest insights on COVID-19 and allergy.